Becoming a World-Class University The case of King Abdulaziz University - Tayeb, Osama; Zahed, Adnan; Ritzen, Jozef; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book written by international experts in the field of educational innovation is a guide for universities to become world-class universities. It contributes to the current international intellectual debate on the future of higher education. It also tells the story of King Abdulaziz University in Jeddah (Saudi Arabia) and its effort to become a world-class university. The book discusses excellence in different aspects such as education, research, community services, strategic planning, knowledge economy and international cooperation.
Roadmap to Become a World-Class University -- International Advisory Boards in the World -- Excellence as Duty -- Excellence in Education -- Excellence in Research -- Excellence in Serving Society and Mankind -- Excellence in Strategic Planning -- Excellence in Innovation and Knowledge Economy -- Excellence in International Cooperation -- Change towards Excellence.
Keywords: Education; International education; Comparative education; School management and organization; School administration; Educational policy; ducation and state; Higher education; Sociology; Education; Higher Education; Administration, Organization and Leadership; Educational Policy and Politics; International and Comparative Education; Knowledge - Discourse; Electronic books